Recent Advances in the Asymmetric Synthesis of α-(Trifluoromethyl)-Containing α-Amino Acids - Aceña, José Luis; Sorochinsky, Alexander E.; Soloshonok, Vadim A. (Synthesis, 2012)
This review article provides a comprehensive update on the development of new methods for the asymmetric synthesis of α-(trifluoromethyl)-α-amino acids, covering the literature from 2006 to mid-February 2012. Most of the methods discussed are based on asymmetric additions across the carbon–nitrogen double bond of the imines derived from esters of 3,3,3-trifluoropyruvic acid. Medium to high levels of stereocontrol can be achieved using phenylglycinol-derived chiral auxiliaries attached to the nitrogen of the corresponding imines. Among the enantioselective approaches, impressive results were achieved through the application of the Strecker reaction using chiral thioureas, as well as chiral Brønsted acids, as organocatalysts.1 Introduction2 Stoichiometric Asymmetric Syntheses of α-(Trifluoromethyl)-α-amino Acids3 Catalytic Asymmetric Syntheses of α-(Trifluoromethyl)-α-amino Acids4 Miscellaneous5 Conclusions
Keywords: asymmetric synthesis; fluorine; amino acids; catalysis; chiral auxiliaries